The mediating influence of liturgy on the way of life – Disposing oppressing powers in oneself and appropriating of compassion towards the other - Kruger, Ferdinand P. (HTS teologiese studies, 2017)
This article presents the authors’ research on the mediating functioning of liturgy and its influence on the change of attributions and attitudes. Within a South African context, voices in connection with decolonisation are becoming more audible. This article is not aimed at an evaluation of the positives or negatives of colonisation or decolonisation. It rather intends to show that liturgy can contribute to this debate by helping people to be conscious of their attributions and attitudes regarding other people. In this regard, liturgy can help people to understand their own identity, an identity that is continuously forming and changing in the light of the attitude in the mind of Christ. People have different attributes on societal issues like, inter alia, decolonisation. Liturgy that is concerned with what is happening in society could contribute towards an attitude or attribute change regarding a liturgy of hospitality towards the other. The main research question for this investigation is: In what way does liturgy as a way of life have the potential to influence people’s attributes and attitudes regarding breaking free from oppressing powers in oneself towards the other in every sphere of life? The research first presents a qualitative literature review to understand this matter. The authors utilise two of Heitink’s phases, namely a hermeneutical understanding of what is happening, and liturgical directives for change. Perspectives from Philippians 2:5–11 are provided to highlight the role of the mind of Christ and of discernment. The article concludes with directives that could possibly influence change regarding attributes and attitudes towards other people.